Wind impairs pit trap construction and hunting success in a pit‐building predator. (15th April 2022) - Miler, K.; Scharf, I.
Abstract: Animals require a set of abiotic conditions to survive and reproduce. When one of these requirements is not met, the animal's performance is impaired. The most often studied abiotic factor is temperature but less is known on other such factors. We examined, here, the effect of wind on the hunting performance of pit‐building predators, insect larvae that dig pit traps in loose soil to hunt arthropod prey. We used wormlions (Diptera: Vermileonidae) as a case study. Pit‐building predators depend on their immediate environment for efficient pit construction and maintenance. For example, they require dry suitable substrate (loose soil) comprised of particles of a specific size range. Because wind blows loose soil and impairs pit construction and maintenance, we expected strong negative effects of wind on pit design and hunting success. Wind destroyed both artificial pit traps and wormlion‐dug pits by moving sand into the pits and reducing their slopes—an important parameter of pits in terms of prey capture. Wormlions also attempted less frequently to attack the prey when the wind was blowing compared to the control and, among the wormlions responding, such response took place later, allowing the prey to escape. We expected wormlions to relocate away when exposed to the wind, but this did not hold true. This result is in line with the generally low relocation rate in wormlions. We suggest that wind has strong negative effects on the performance of pit builders in nature. Sites that provide at least partial protection from wind should be preferred for pit establishment. Abstract : We examined the effect of wind on the hunting performance of pit‐building predators, insect larvae that dig pit traps in loose soil to hunt arthropod prey. Wind destroyed the pits by moving sand into them and reducing their slopes – an important parameter in terms of prey capture. Pit builders attempted less frequently and more slowly to attack the prey when the wind was blowing compared to the control. However, in contrast to our expectation, pit builders did not relocate away when exposed to wind. In the photo: Two sites prone to wind in which pit‐building predators dig pits. Left: Antlions on Massada mountain, southern Israel. Right: Wormlions in Tel Aviv University, central Israel, which is located on a hill.